2014
DOI: 10.1186/1471-230x-14-23
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin transporter gene polymorphism (5-HTTLPR) and irritable bowel syndrome: a meta-analysis of 25 studies

Abstract: BackgroundThe results of previous studies assessing the association between the 5-HTTLPR polymorphism of serotonin transporter gene and irritable bowel syndrome (IBS) are inconsistent. The aim of this study was to clarify the association between the 5-HTTLPR mutation and the presence of IBS and its subtypes with a meta-analysis of 25 studies.MethodsA thorough search for case–control studies evaluating the association between the 5-HTTLPR polymorphism of serotonin transporter gene and the presence of IBS was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 38 publications
3
41
0
3
Order By: Relevance
“…Moreover, L allele and L/L genotype were significantly associated with increased IBS-C risk in the East Asian population. 30 The genotypic association between the L/L genotype and not only IBS-C but also IBS-M may result from possible misclassification of IBS-M or spectrum disorder of IBS itself. IBS-M is a highly heterogeneous due to range of symptoms that are similar to those in IBS-D and IBS-C, 31 this would cause a large proportion of patients remains IBS-M.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, L allele and L/L genotype were significantly associated with increased IBS-C risk in the East Asian population. 30 The genotypic association between the L/L genotype and not only IBS-C but also IBS-M may result from possible misclassification of IBS-M or spectrum disorder of IBS itself. IBS-M is a highly heterogeneous due to range of symptoms that are similar to those in IBS-D and IBS-C, 31 this would cause a large proportion of patients remains IBS-M.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced SERT expression and function result in excess 5‐HT, along with motor, sensory, and secretary dysfunctions of the gut, which lead to development of diarrhea and abdominal pain associated with the pathogenesis of IBS . Furthermore, polymorphisms in the promoter region of the SERT gene influence the expression of SERT in colonic mucosa, which also plays a key role in the pathogenesis of IBS patients . Symptoms resembling IBS are known to occur in cases of IBD; thus, a common pathogenesis for IBS and IBD is possible.…”
Section: Introductionmentioning
confidence: 99%
“…In investigations of SERT polymorphisms in IBS, a meta-analysis of seven studies concluded that 5-HTTPLR genotypes are unrelated to IBS, while others reported evidence of an association when patients were stratified by predominant clinical symptoms [29]. The most recent meta-analysis of 25 such studies concluded that the L/L genotype of 5-HTTLPR is associated with an increased risk of developing constipation-predominant IBS (IBS-C) [30]. 5-HTTLPR genetic polymorphisms also may provide evidence for the efficacy of serotonin-based therapies for specific subtypes of IBS.…”
mentioning
confidence: 99%